The Development of Islamic Economic Politics in Sharia Banking in The Reform Era to Date in Indonesia - Luthfiana Basyirah; Muhamad Hamam Nasiruddin; Fathor Rozi; Badrus Syamsi MS (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The article aims to determine the relationship between the Indonesian state and the Islamic economy related to the influence of the Indonesian government's Islamic political economy in the development of sharia economic practices in society, especially in the reform era. The research method used in this study is a qualitative approach with the type of library research. The data sources used are secondary data sources, obtained from the collection of documentation related to the development of Islamic economic politics in Islamic banking in the reform era in Indonesia. The data that has been collected is analyzed through content analysis and the validity of the data is checked through triangulation of secondary data sources. This article uses the political theory of Islamic economics in the reform era and the theory of the development of sharia banking regulations by Dr. Itang, M.Ag. This article finds that the influence of the State of Indonesia with its political economy oriented to the Islamic economic system in developing Islamic economic practices is very significant. This also shows that there is a rapid progress in the practice of Islamic economics, especially in the field of Islamic banking, which is increasingly attracting the whole community to invest in Islamic banking because the formal regulations are very clearly stated in the Act. In addition, the development of Islamic political economy has also greatly influenced the development of other non-banking Islamic financial institutions, such as sharia insurance, sharia capital markets, sharia bonds, sharia mutual funds, and Islamic microfinance institutions, and Islamic public finance after the Indonesian state supported them in many things, especially through formal regulation.